Odpowiedź :
Odpowiedź:
[tex]a) 3a+2a*5a-7a^{2} +\frac{6a^{2} }{3} =3a+10a^{2} -7a^{2} +\frac{6a^{2} }{3}=3a+3a^{2} +\frac{6a^{2} }{3} =3a+7a^{2} \\b) 3x^{2} +2x*(-3x)+4x^{2} +\frac{15x}{3}=3x^{2} -6x^{2} +4x^{2} +\frac{15x}{3} =x^{2} +5x\\[/tex]
[tex]c) -4y*5x+2x*5-3x*2y+\frac{8xy}{2} =-20xy+10x-6xy+4xy=-6xy+10x\\d) \frac{10ab}{5} +5b^{2} -2b*5b-3b^{2} *2-2ab=2ab+5b^{2}-10b^{2} } -6b^{2} -2ab= 11b^{2}[/tex]
25-250b^2b^2+2250
Szczegółowe wyjaśnienie:
Odpowiedź:
3a+2a*5a-7a^2+6a^2/3 /obie strony równania razy 3
9a+6a*15a-21a^2+6a^2
15a*15a-21a^2+6a^2
15a*15a-15^2
225a-15^2
3x^2+2x*(-3x)+4x^2+15x/3 /obie strony równania razy 3
9x^2+6x*-9+12x^2+15x
21x^2+6x*-9+15x
21x^2-54x+15x
21x^2-39x
-4y*5x+2x*5-3x*2y+8xy/2
-20xy+10x-6xy+8xy/2
-26xy+8xy+10x
-18xy+10x
10ab/5+5b^2-2b*5b-3b^2*2-2ab/obie strony równania razy 5
10ab+25b^2-10b*25b-15b^2*10-10ab
25b^2-250b^2+2250b^2
2025^2